2007
DOI: 10.1002/chem.200601656
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐State Hosts by the Template Polymerization of Columnar Liquid Crystals: Locked Supramolecular Architectures around Chiral 2‐Amino Alcohols

Abstract: The cross-linking of multicomponent liquid crystals could be applied to the synthesis of nanometer-sized porous materials with a well-defined structure. In this work we demonstrate the template polymerization of columnar liquid crystals composed of the salts of a carboxylic acid and enantiopure 2-amino alcohols, and the application of one of them as a solid-state host. The salts of 3,4,5-tris(11-acryloyloxyundecyloxy)benzoic acid with (S)-2-amino-1-propanol and with (1R,2S)-norephedrine showed hexagonal and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 44 publications
(9 reference statements)
0
39
1
2
Order By: Relevance
“…These results showed that Hbonding interactions can be used to bind guest molecules in materials by molecular imprinting. More recent studies have demonstrated that the polymer porous material also readily incorporates other guest molecules with sizes that fit in the chiral nanochannels [67]. Detailed studies indicate that modification of the polymer porous material has large effects on properties such as structural order, guest recognition and release, and its repetitive switching [64,68].…”
Section: Hydrogen Bonding In Liquid Crystals As Nanoporous Networkmentioning
confidence: 98%
“…These results showed that Hbonding interactions can be used to bind guest molecules in materials by molecular imprinting. More recent studies have demonstrated that the polymer porous material also readily incorporates other guest molecules with sizes that fit in the chiral nanochannels [67]. Detailed studies indicate that modification of the polymer porous material has large effects on properties such as structural order, guest recognition and release, and its repetitive switching [64,68].…”
Section: Hydrogen Bonding In Liquid Crystals As Nanoporous Networkmentioning
confidence: 98%
“…Therefore, in situ reactions in LCs would lead to a new type of tailored micro-environment, which may realize highly efficient/selective molecular recognitions and chemical reactions. This review summarizes our recent effort to develop a new class of micro-environment based on the in situ reactions in LCs [16,17,18,19,20]. In relation to our studies, we also provide an overview of notable works related to LC-template reactions, from historically important reports to recent trends.…”
Section: Introductionmentioning
confidence: 98%
“…Clark and coworkers reported a class of fluid polar smectic liquid crystals in which local splay prevails in the form of periodic supermolecular-scale polarization modulation stripes coupled to layer undulation waves [216]. Other recent examples on self-assembled liquid crystal materials are also available [217][218][219][220][221].…”
Section: Gels and Liquid Crystalsmentioning
confidence: 99%